Translation and Validation of Childhood Healthcare Assessment Questionnaire in Urdu Language for Juvenile Idiopathic Arthritis - Zuhab Bin Ashraf, Shoaib Waqas, Rida Khawar Dar, Muhammad Tariq, Muhammad Nouman Tabassum, Qurat Ul Ain Sherazi (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To translate and validate Childhood Healthcare Assessment Questionnaire (CHAQ) in Urdu language and assess its psychometric properties for cross cultural adaptation. Methods: The Childhood Healthcare Assessment Questionnaire (CHAQ) was translated into the target language of Urdu by two independent translators, one of whom was familiar with the questionnaire’s concept while the other was not, and the two translations were then compared as part of a cross-cultural linguistic validation study. These two initial translations of the questionnaire were blindly reversed, and the results were compared1. The pre-final version of the translated version underwent thorough psychometric testing in a sample of 38 members of the target population (parents of children with juvenile idiopathic arthritis at Ghurki Trust and Teaching Hospital, Lahore) who satisfied the inclusion requirements. The final version was reviewed by an expert panel. Parents’ prior approval was obtained before testing. Results: The Cronbach’s alpha for the Urdu version of CHAQ was calculated as 0.993 after testing on the population showing excellent internal consistency. For test-retest reliability, Pearson correlation ranged from (0.378–0.956).The inter-item correlation of the Urdu version of CHAQ after applying to the targeted population has a mean value of 1.177, a minimum value of 0.056, a maximum value of 4.00, a variance value of 0.723, and a range of 3.944. The scale statistics have a mean value of 103.55, a variance of 1462.37, a standard deviation of 38.241, and a total number of items of 88.The intraclass correlation coefficient ranges from 0.606-0.993. Conclusion: The Childhood Healthcare Assessment Questionnaire in Urdu is a screening tool for parents of children with juvenile idiopathic arthritis since it has adequate inter-item correlation values and great internal consistency. Keywords: Childhood Healthcare Assessment Questionnaire (CHAQ), Juvenile Idiopathic Arthritis (JIA), Reliability, Validity, Cross-cultural adaptation